Misères et splendeurs d’un mendicant dans 'Le Seigneur vous le rendra' de Mahi Binebine - Mohamed Semlali (Interlitteraria)
Mahi Binebine is a Moroccan novelist with more than twelve novels to his credit. He is also a great painter whose paintings can be found in the most famous collections, notably in the permanent collection of the Guggenheim Museum in New York. For him, painting and writing evolve together and deal with the same issues. In his novel, The Lord Will Pay You Back, Binebine takes up the theme of the suffocation of the individual who tries to resist the alienating forces that crush him (misery, predation). We propose to read this story as a picaresque tale with symbolic significance: the protagonist, forced to beg from birth, bears the brunt of his own mother’s monstrosity and dislike, worthy of the worst of the fairy tales. Driven by poverty, the mother takes possession of her child’s body and sculpts a deformed being that will be exhibited in the main square of Marrakech to earn a living. If the monstrous is here inseparable from the tale, it also inscribes the hero in a process of transformation made possible by intellectual (literature) and sentimental (love) learning. Thus the protagonist goes from being a simple fairground beast who flaunts his disproportionate physique for a few coins to becoming a storyteller, a fabulator, a creator of worlds. In the meantime, the tale gives way to the novel and the child, now an adult, regains a certain bodily normality, which is not a guarantee of happiness. If the marvellous is not completely evacuated, if the narrator claims a part of fantasy in his story, the novel is there to remind us that a literary work is also a reflection on the human condition of those left behind and on the alienation of the individual who must redouble his ingenuity to assert himself as a singular and independent being.